Prevalence of Pulmonary Embolism and Deep Venous Thromboembolism in Patients With Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Han, Weihong; Wang, Minghang; Xie, Yang; Ruan, Huanrong; Zhao, Hulei; Li, Jiansheng (Frontiers in Cardiovascular Medicine, 2022)
Background Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) increases the risk of pulmonary embolism (PE) and deep venous thrombosis (DVT). AECOPD combined with PE and DVT poses challenges for treatment and management. This necessitates prevention and management to estimate the overall prevalence of PE and DVT among patients with AECOPD and to identify the risk factors. Methods We searched the PubMed, Embase, and Cochrane Library databases from their inception to January 9, 2021 and extracted the data from the included studies. The risk of bias was assessed for each study. We separately calculated the prevalence of PE and DVT in patients with AECOPD. Subgroup analysis and meta-regression analyses were performed to determine the sources of heterogeneity. Furthermore, we assessed the publication bias. Results The meta-analysis included 20 studies involving 5,854 people. The overall prevalence of PE and DVT among patients with AECOPD was 11% (95% CI: 0.06–0.17) and 9% (95% CI: 0.06–0.12), respectively. Subgroup analysis demonstrated that the prevalence of PE among patients with AECOPD was 12, 2, 7, and 16% in the European, South-East Asia, Western Pacific, and Eastern Mediterranean regions, respectively, and the DVT was 10, 9, 9, and 4%, respectively. The prevalence of PE among patients with AECOPD aged ≥ 70 and <70 years old was 6 and 15%, respectively, and the DVT was 8 and 9%, respectively. The prevalence of PE among patients with AECOPD diagnosed within 48 h and other times (beyond 48 h or not mentioned) was 16 and 6%, respectively, and DVT was 10 and 7%, respectively. Conclusion The pooled prevalence of PE and DVT among patients with AECOPD was insignificantly different between the different age groups and the WHO regions. However, the early diagnosis was associated with a higher prevalence of PE. Clinicians and the public need to further improve the awareness of prevention and management for PE and DVT among patients with AECOPD. Systematic Review Registration PROSPERO, identifier CRD42021260827.